2020
DOI: 10.3390/medicina56120678
|View full text |Cite
|
Sign up to set email alerts
|

Update on COVID-19 Myocarditis

Abstract: Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) gained worldwide attention at the end of 2019 when it was identified to cause severe respiratory distress syndrome. While it primarily affects the respiratory system, we now have evidence that it affects multiple organ systems in the human body. Cardiac manifestations may include myocarditis, life threatening arrhythmias, acute coronary syndrome, systolic heart failure, and cardiogenic shock. Myocarditis is increasingly recognized as a complication o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(74 citation statements)
references
References 66 publications
0
56
0
5
Order By: Relevance
“…Thus, in patients with COVID-19 infection, a garden variety of ACS-NNOCA may be observed ranging from ruptured pre-existing or new atherosclerotic plaques to other ischemic or non-ischemic syndromes, like TTC or acute myocarditis. 57,64,73 -75,77 -79 Importantly, compared with the non-COVID-19 patients, the prevalence of ACS-NNOCA in COVID-19 patients appears to be much higher, reported at ∼33%-55% of patients with COVID-19 presenting with STEMI, 66,67,80 when ACS-NNOCA has been reported to occur in 3.5%-14.5% in non-COVID patients presenting with ACS; 10 the reasons behind this discrepancy have not been elucidated (see discussion on mechanisms below). Notably, the risk of sudden cardiac death (SCD) in patients with ACS-NNOCA remains a major concern; myocardial ischemia, inflammation, and fibrosis are probably at the core of the SCD risk in these patients.…”
Section: Acute Coronary Syndromes With Normal or Near-normal Coronariesmentioning
confidence: 99%
“…Thus, in patients with COVID-19 infection, a garden variety of ACS-NNOCA may be observed ranging from ruptured pre-existing or new atherosclerotic plaques to other ischemic or non-ischemic syndromes, like TTC or acute myocarditis. 57,64,73 -75,77 -79 Importantly, compared with the non-COVID-19 patients, the prevalence of ACS-NNOCA in COVID-19 patients appears to be much higher, reported at ∼33%-55% of patients with COVID-19 presenting with STEMI, 66,67,80 when ACS-NNOCA has been reported to occur in 3.5%-14.5% in non-COVID patients presenting with ACS; 10 the reasons behind this discrepancy have not been elucidated (see discussion on mechanisms below). Notably, the risk of sudden cardiac death (SCD) in patients with ACS-NNOCA remains a major concern; myocardial ischemia, inflammation, and fibrosis are probably at the core of the SCD risk in these patients.…”
Section: Acute Coronary Syndromes With Normal or Near-normal Coronariesmentioning
confidence: 99%
“…Several studies indicated that cardiac events and myocarditis were common in hospitalized patients due to COVID-19 infection and this was attributed to the elevation in cardiac enzymes as troponin and lactate dehydrogenase (LDH) [ 51 , 52 ]. On the other hand, elevation in the level of troponin was observed in hospitalized COVID-19 patients taking remdesivir.…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2-induced myocarditis is a relatively rare complication that has been reported in multiple case reports [10][11][12][13][14]. Symptoms can range from shortness of breath to cardiogenic shock and fulminant myocarditis, a lifethreatening presentation [15]. In milder cases, patients have responded well to standard therapy of congestive heart failure, including a beta-blocker and angiotensin-converting enzyme inhibitor (ACEI) [11].…”
Section: Discussionmentioning
confidence: 99%